2009
DOI: 10.1152/japplphysiol.90349.2008
|View full text |Cite
|
Sign up to set email alerts
|

Early brain swelling in acute hypoxia

Abstract: Acute mountain sickness (AMS) and high-altitude cerebral edema share common clinical characteristics, suggesting cerebral swelling may be an important factor in the pathophysiology of AMS. Hypoxia and hypocapnia associated with high altitude are known to exert strong effects on the control of the cerebral circulation, yet how these effects interact during acute hypoxia, and whether AMS-susceptible subjects may have a unique response, is still unclear. To test if self-identified AMS-susceptible individuals show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 36 publications
5
43
0
Order By: Relevance
“…Some previous studies suggested that MRI signs of cerebral subedema may be observed as early as during the first hour of hypoxic exposure. 5,6 In the present study, white-matter volume already increased significantly after 30 minutes of hypoxic exposure. This time point coincides with significant and near maximal reduction in cerebral oxygenation measured by near-infrared spectroscopy during a 4-hour hypoxic exposure (FiO 2 = 0.12) at rest.…”
Section: Correlationssupporting
confidence: 53%
See 2 more Smart Citations
“…Some previous studies suggested that MRI signs of cerebral subedema may be observed as early as during the first hour of hypoxic exposure. 5,6 In the present study, white-matter volume already increased significantly after 30 minutes of hypoxic exposure. This time point coincides with significant and near maximal reduction in cerebral oxygenation measured by near-infrared spectroscopy during a 4-hour hypoxic exposure (FiO 2 = 0.12) at rest.…”
Section: Correlationssupporting
confidence: 53%
“…The absence of significant change in ADC after 30 minutes of exposure suggests that edema is not responsible for this early increase in whitematter volume. From unchanged CBF, it may be extrapolated that cerebral blood volume was also unchanged, 6 but the relationship between CBF and cerebral blood volume may not be always straightforward especially with potential changes in venous blood volume. 7 We recently showed that prefrontal total haemoglobin concentration measured by near-infrared spectroscopy increased within 30 minutes of hypoxic exposure at rest, suggesting that an increase in cerebral blood volume may occur after short duration hypoxic exposure and might underlie an increase in cerebral volume as observed in the present study.…”
Section: Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…found elevated brain volume, particularly gray matter, during periods of hypoxemia, [9][10][11] which is unlikely to be due to the accumulation of brain edema. [12][13][14] Furthermore, lumbar pressure is elevated in individuals with suspected high-altitude cerebral edema, 15 but not in individuals with AMS after 18 hours in normobaric hypoxia.…”
mentioning
confidence: 83%
“…The first step down the path to brain swelling is hypothesized to be increased cerebral blood flow and associated increased cerebral blood volume, which directly produces brain swelling-leading to increased capillary pressure and cerebral edema. We previously found that increased cerebral blood flow is a common outcome of ascent to high altitude, 17 as is cerebral swelling and reduced CSF volume, 18 but neither was associated with a greater propensity to develop AMS. An alternate hypothesis for brain swelling and symptoms of AMS may relate to compromised cerebral energy status.…”
Section: Diffusion-weighted Mri Changes In Acute Mountain Sickness Jsmentioning
confidence: 98%